COPD Maintenance Therapy with Tiotropium/Olodaterol Compared with Tiotropium: An Analysis in the Absence of Additional ICS Therapy. (2nd September 2020) - Calverley, Peter M. A.; Hoz, Alberto de la; Xue, Wenqiong; Ferguson, Gary T.; Miravitlles, Marc
Abstract: The American Thoracic Society guidelines recommend long-acting β2 -agonist (LABA)/long-acting muscarinic antagonist (LAMA) dual bronchodilation over LAMA or LABA monotherapy as maintenance therapy for patients with chronic obstructive pulmonary disease suffering from dyspnea or exercise intolerance. Previous studies, which included patients receiving background inhaled corticosteroids (ICS), have shown the benefits of dual bronchodilation over monotherapy. This analysis aimed to confirm the benefits of LAMA/LABA over LAMA alone, without any confounding effects from ICS use. This pooled post hoc analysis compared the efficacy of tiotropium/olodaterol with tiotropium alone in patients from the TONADO ® and OTEMTO ® clinical trials who were not receiving ICS at study entry or during the studies. We analyzed change from baseline in trough forced expiratory volume in 1 s (FEV1 ), St. George's Respiratory Questionnaire (SGRQ) score and Transition Dyspnea Index (TDI) score in all patients, by Global Initiative for Chronic Obstructive Lung Disease (GOLD) stage, baseline SGRQ score, and Baseline Dyspnea Index score. In this analysis of 1596 patients, tiotropium/olodaterol improved trough FEV1, SGRQ and TDI compared with tiotropium alone. The observed mean differences were: trough FEV1, 0.054 L (95% confidence interval [CI] 0.036, 0.073; p  < 0.001); SGRQ, −1.918 (95% CI −2.994, −0.843; p  < 0.001); and TDI, 0.575 (95% CI 0.301, 0.848; p  < 0.001). Similar improvements were seen in each of the subgroup analyses. Tiotropium/olodaterol therapy significantly improved lung function, symptoms and health status compared with tiotropium alone. In a population free from ICS treatment, these data confirm the benefits of dual bronchodilation versus monotherapy.